Nanomaterial synthesis, an enabler of amyloidosis inhibition against human diseases. Issue 27 (8th July 2020) - Andrikopoulos, Nicholas; Li, Yuhuan; Cecchetto, Luca; Nandakumar, Aparna; Da Ros, Tatiana; Davis, Thomas P.; Velonia, Kelly; Ke, Pu Chun
Abstract : We summarize current strategies for the synthesis and construction of nanoparticle inhibitors and probes against pathogenic amyloidosis. Abstract : Amyloid diseases are global epidemics with no cure currently available. In the past decade, the use of engineered nanomaterials as inhibitors or probes against the pathogenic aggregation of amyloid peptides and proteins has emerged as a new frontier in nanomedicine. In this Minireview, we summarize for the first time the pivotal role of chemical synthesis in enabling the development of this multidisciplinary field.